Uso de atividades gamificadas no ensino técnico profissional: uma proposta pedagógica - Silva, Ricardo da Silva e (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this dissertation is to present a classroom experience by applying the concepts of gamification in the construction of a pedagogical practice in a group of a professional technical education, from Logistics Technician course, seeking to validate the concepts of gamification and envision its efficiency in the development of efficiency and skills. The experiment takes place in three stages, which in a first moment the entertaining game Age Of Empires, was used with educational purposes, and in the second stage the educational game Beer Game and in the last stage of the experiment the serious online game Caminhos do Conhecimento, developed for this research, with educational purposes. These three distinct stages were related to each other through the elements from games like ranking by scores, cooperation and constantly feedback, among others. This research, also aims analyze students satisfaction about their gamified classes, as an alternative learning method, through the analysis of collected data from questionnaires applied to students involved in this research.
Keywords: Gamificação; Ensino profissional; Educação; Gamification; Professional education; Education; ACCNPQ::Ciências Humanas::Educação